Lapa verde, víctima del manejo forestal insostenible - Chassot, Olivier; Monge, Guiselle; Powell, George; Palminteri, Suzanne; Alemán, Ulises; Wright, Pamela; Adamek, Krista (Revista de Ciencias Ambientales, 2001)
No disponible/Not available